Evaluation of state support programs for small business: A regional aspect - Podshivalova M.V. (Ural State University of Economics, 2019)
This paper aims to evaluate SME support programs in the context of institutional theory. The methodological basis of the study is the theory of transaction costs, which makes it possible to develop the theoretical aspects of evaluating the effectiveness of state programs by including a new factor in the analysis, i.e. various types of the funds recipients’ transaction costs. The authors raise question about the effectiveness of the applied entrepreneurship support programs using the case study of Chelyabinsk and Chelyabinsk region. We analyse the main requirements to applicants, time costs for obtaining subsidies, as well as feedback indicators. On the one hand, we reveal that government bodies impose strict requirements for applicants. On the other hand, the demand for government financial support from SMEs is low. The researchers assess transaction costs of subsidies recipients by transforming time costs into financial costs and conclude that the level of SME transaction costs when submitting applications is insignificant. The main reason behind SME’s reluctance to participate in the tender for the allocation of budget funds is a high level of transaction costs of a different nature, that is losses associated with stepping out of the “shadow” when providing information for authorities. The practical application of the results is aimed at improving the adequacy of methods for evaluating the effectiveness of SME support programs for the institutional constraints of the Russian small business.